Beneficial effects of Tinospora Cordifolia on haematological profiles exposed to CCL4 intoxicated mice (Funded Work) - RADHIKA SRIVASTAVA; SUSHMA (International Journal of Pharma and Bio Sciences, 2019)
This study was carried out to evaluate invivo protective role of aqueous ethanol leaves extract of Tinospora cordifolia(TC) on the toxic effects of CCl4 on the haematological values. The CCl4-treated (5 mg/kg body weight, intraperitoneal, once daily) male albino mice concurrently received either T. cordifolia stem or leaves extracts (200 and 400 mg/g body weight, orally, once daily) for 21 days. The animals exposed to CCl4 showed a significant decrease in the haematological profile, and that was rescued by aqueous extract T. cordifolia. A significant increase in SGPT, SGOT, protein, leucocyte count, polymorphs, lymphocyte, eosinophils, monocytes, basophils percentage and erythrocyte sedimentation ESR was also noticed. These influences of CCl4 was prevented by concurrent daily administration of T. cordifolialeaves extract. The extract of T. cordifolia in CCl4 intoxicated mice enhanced the SGOT up to 125 ± 1.02 IU, reduced SGPTupto61.46 ± 1.38 Iµ/dl and SALP 174.54 ± 1.02 Iµ/dl after CCl4 intoxication for 21 days. These results suggested that simultaneous supplementation of T. cordifolia protects against CCl4 intoxication.